Interactive Mobile Health Intervention and Blood Pressure Management in Adults: A Meta-Analysis of Randomized Controlled Trials. Issue 3 (September 2019) - Lu, Xiaomei; Yang, Huijun; Xia, Xue; Lu, Xiangfeng; Lin, Jinchun; Liu, Fangchao; Gu, Dongfeng
Abstract : Despite the availability of effective drugs, blood pressure (BP) control remains poor among most populations. To explore the effects of interactive mobile health (mhealth) intervention on BP management and find out the optimal target population, we performed a systematic review and meta-analysis of randomized controlled trials to estimate the pooled effects of mhealth intervention on BP control. PubMed, EMBASE, Cochrane Library, and CNKI were searched to identify eligible randomized controlled trials published between January 15, 2007 and April 28, 2019, and bibliographies of eligible articles were further reviewed. Random-effect models were utilized to pool estimates of net changes in systolic BP and diastolic BP between mhealth intervention group and control group. Eleven randomized controlled trials met the inclusion criteria, with a total sample size of 4271 participants. Compared with the control group, mhealth intervention was associated with significant changes in systolic BP and diastolic BP of −3.85 mm Hg; 95% CI, −4.74 to −2.96 and −2.19 mm Hg; 95% CI, −3.16 to −1.23, respectively. Subgroup analyses revealed consistent effects across study duration and intervention intensity subgroups. In addition, participants with inadequate BP control at recruitment might gain more benefits with mhealth intervention. Therefore, interactive mhealth intervention may be a useful tool for improving BP control among adults, especially among those with inadequate BP control. Abstract : Supplemental Digital Content is available in the text.